2021
DOI: 10.1038/s41467-021-24333-z
|View full text |Cite
|
Sign up to set email alerts
|

Iron-dependent apoptosis causes embryotoxicity in inflamed and obese pregnancy

Abstract: Iron is essential for a healthy pregnancy, and iron supplementation is nearly universally recommended, regardless of maternal iron status. A signal of potential harm is the U-shaped association between maternal ferritin, a marker of iron stores, and risk of adverse pregnancy outcomes. However, ferritin is also induced by inflammation and may overestimate iron stores during inflammation or infection. In this study, we use mouse models to determine whether maternal iron loading, inflammation, or their interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…In this sense, Fisher et al. ( 74 ) demonstrated that iron overload causes increased expression of HO-1 in placental endothelial cells, and exposure to iron overload and inflammation have a synergistic effect on the induction of oxidative stress and cell death in a TNF-α-dependent manner. In fact, increased levels of circulating TNF have been associated with fetal loss in the first trimester of human pregnancy ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Fisher et al. ( 74 ) demonstrated that iron overload causes increased expression of HO-1 in placental endothelial cells, and exposure to iron overload and inflammation have a synergistic effect on the induction of oxidative stress and cell death in a TNF-α-dependent manner. In fact, increased levels of circulating TNF have been associated with fetal loss in the first trimester of human pregnancy ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNF-α is produced by adipose tissue and its secretion correlates with the degree of adiposity [144]. In a model of obese pregnant mice, Fisher et al showed that excess iron promotes TNF-α production and embryotoxicity [6].…”
Section: Obesity and Iron Deficiencymentioning
confidence: 99%
“…However, excess iron generates reactive oxygen species through the Fenton reaction [2], leading to cellular and tissue injury [3,4]. This can ultimately lead to cell death by ferroptosis [5] or iron-dependent apoptosis [6]. Both excess iron and iron deficiency can be observed in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Serum ferritin is a protein that indicates the level of iron reserve in the body ( 3 ). Poor ferritin level is a common nutritional problem during pregnancy and is associated with inadequate intake anemia or certain chronic diseases ( 4 ). Ferritin itself has important physiological activities which is not only a carrier of iron ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iron, on the other hand, is a powerful pro-oxidant that catalyzes the production of reactive oxidative species (ROS) ( 5 ). Excess iron intake can lead to impaired placenta function because of oxidative damage ( 4 ). Existing epidemiological evidence demonstrates that higher serum ferritin is associated with an increased risk of LBW in late pregnancy ( 6 ).…”
Section: Introductionmentioning
confidence: 99%